Effects of media literacy education about television food advertising on school children / Zalma Abdul Razak - Abdul Razak, Zalma (2015)
Media literacy education is one of the strategies to reduce the influence of television food advertising. However, there is limited study done to assess its effectiveness. The objective of this study was to determine the effects of media literacy education on television food advertising among school children. This study used a quasixperimental design involving two groups of children-intervention (N == 59) and control (N == 63) - with the mean age of 128 (3.37) months. The children in the intervention group were given a 10-lesson media literacy education conducted in three weeks during school hours. The children in the control group attended normal classes.Data were collected before the intervention (pre-intervention), 2 weeks after the intervention (2-week follow-up) and four weeks after the intervention (4-week followup), using a validated questionnaire. The ANOVA indicated that the children's knowledge on television food advertising, knowledge on healthier food and preference for healthier food increased significantly, F (1.74,83.38) == 22.46,p < 0.001; F (1.22, 58.30) == 11.41,p == 0.001; and F (1.34,64.50) == 13.10,p < 0.001; and the children's consumption of commonly advertised food decreased significantly, F (2, 96) == 9.70, p < 0.001; after the intervention. The ANOVA also indicated that there were significant differences in knowledge on television food advertising, knowledge on healthier food and preference for healthier food between the intervention and control group, F (2, 202) == 15.12, p < 0.001; F (1.42, 143.47) == 3.88, p == 0.036; and F (1.69, 170.61) == 10.38, p < 0.00 1. However, there was no significant difference in the consumption of commonly advertised food between the two groups, F (2, 202) == 2.65, p == 0.073. This study also indicated that there was no significant correlation found at all the three phases between knowledge on television food advertising and consumption of commonly advertised food, r == - 0.21, p > 0.05, r == 0.16, p > 0.05, r == - 0.16, p > 0.05 and between knowledge on healthier food and consumption of commonly advertised food, r == - 0.25, p > 0.05, r == 0.06, p > 0.05, r == - 0.12, P > 0.05. This study revealed that media literacy education was effective in increasing knowledge on and preference for healthier food. However it was less effective in reducing the consumption of commonly advertised foods among school children.